Perioperative Outcomes of Minimally Invasive Aortic Valve Replacement through Right Anterior Minithoracotomy - Stoliński, Jarosław; Fijorek, Kamil; Plicner, Dariusz; Grudzień, Grzegorz; Kruszec, Paweł; Musiał, Robert; Andres, Janusz (The Thoracic and Cardiovascular Surgeon, 2016)
Background The aim of the study was to analyze perioperative outcomes after minimally invasive aortic valve replacement through right anterior minithoracotomy (RAT-AVR). Patient selection criteria, anesthesia protocol, and surgical technique are presented.Methods A retrospective analysis of 194 patients electively scheduled for RAT-AVR was performed between January 2009 and June 2013. For preoperative planning, computed tomography was performed.Results Among studied patients, there were 48.5% females and 51.5% males with a mean age of 69.9 ± 9.2 years. The predicted mortality calculated with EuroSCORE II was 3.2 ± 0.9%, and observed mortality of RAT-AVR patients was 1.5%. Finally, RAT-AVR surgery was performed on 97.9% of patients (n = 190). Reasons for conversions to median sternotomy were bleeding from aortotomy site (n = 4) and from the right ventricle after epicardial pacing wire placement (n = 1), pleural adhesions (n = 2), and ascending aorta hidden under the sternum (n = 2). The second intercostal space was chosen for surgical access in 97.9% of patients.There were 3.6% reoperations for bleeding: aortotomy place (n = 1), epicardial pacing wire placement (n = 3), right lung tear (n = 2), and intercostal vessels (n = 1). The intensive care unit and hospital length of stays were 1.3 ± 1.2 and 5.7 ± 1.4 days, respectively. Strokes were present in 1.5% of patients. The perioperative complications rate diminished with time, occurring in 44.9% of the patients between 2009 and 2010 and in 15.6% of patients in 2013.Conclusions RAT-AVR can be safely performed without increased morbidity and mortality. Reduced complication rates over time reflect a learning curve.
Keywords: aortic valve; minimally invasive surgery; minithoracotomy; valve surgery